PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN DISIPLIN KERJA GURU TERHADAP MOTIVASI BERPRESTASI GURU SD SWASTA - Evryyanti Tiurma Pakpahan; Aunurrahman Aunurrahman; M Chiar (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research was to determine the influence of principal leadership styles though achievement motivation teacher in private elementary school sub district South Pontianak; This research was using the research quantitative with descriptive with descriptive analysis. Subject of the research were teachers at private Elementary School Sub District South Pontianak by the number are 72 teachers. Measuring instrument used in data the principal Leadership style questionnaire, discipline teacher job questionnaire, and achievement motivation teacher questionnaire was Likert’s Scale. For testing the hypothesis in this thesis used to technique of correlation and analyzed by regression technique. The results from correlation analyzed and regression technique found that: (1) there was an influence from principal leadership style though achievement motivation teacher with value 54,4 % (2) there was an influence discipline teacher job though achievement motivation teacher with value 24,3 % (3) there was an influence from the principal leadership style and discipline teacher job though achievement motivation teacher with value 26,6%. Keywords: Achievement Motivation Teacher, Discipline Teacher Job, Principal Leadership Style